Microglial inhibition of neuroprotection by antagonists of the EP1 prostaglandin E2 receptor - Carlson, Noel G (BioMed Central, 2009)
BACKGROUND: The EP1 receptor for the prostanoid PGE2 is a G-protein coupled receptor that has been shown to contribute to excitotoxic neuronal death. In this study we examined the influence of non-neuronal cells on neuroprotective properties of EP1 receptor antagonists (Ono 8711 and SC 51089). METHODS: Primary neuronal cultures systems with or without non-neuronal cells were used to examine how the neuroprotective properties of EP1 antagonists were influenced by non-neuronal cells. The influence of astrocytes or microglia were individually tested in excitotoxicity assays using a co-culture system with these cells grown on permeable transwell inserts above the neuronal-enriched cultures. The influence of microglia on PGE2 synthesis and EP1 receptor expression was examined. RESULTS: EP1 antagonists were neuroprotective in neuronal-enriched cultures (> 90% neurons) but not in mixed cultures (30% neurons plus other non-neuronal cells). Co-cultures of microglia on permeable transwell inserts above neuronal-enriched cultures blocked neuroprotection by EP1 antagonists. Incubation of microglia with neuronal-enriched cultures for 48 hours prior to NMDA challenge was sufficient to block neuroprotection by EP1 antagonists. The loss of neuroprotection by EP1 antagonists was accompanied by a decrease of neuronal EP1 expression in the nucleus in cultures with microglia present. CONCLUSION: These findings demonstrate microglial modulation of neuronal excitotoxicity through interaction with the EP1 receptor and may have important implications in vivo where microglia are associated with neuronal injury.